USABILITY TESTING PADA E-LEARNING UNIVERSITAS TEKNOLOGI YOGYAKARTA BAGIAN MENU PROFILE - Aldora Gavrila Faiq; Bonaventura Exsa Berta Putra; Ikhsan Shihab Budin; Ferida Yuamita (JURNAL ILMIAH NUSANTARA, 2024)
E-learning that uses the web has now become an important part in achieving the success of an educational institution, but many services that use the web still find it difficult to use it, even it is not attractive and does not function as the web is used. The reason a web page needs to be measured is to know the quality of the website from the users. By doing this research, we can determine the usability of the e-learning web to Yogyakarta Technological University students who are often used during learning, the method we use is to use usability testing which will determine the level of usability of the e-learning web.